Analysis of recurrence and metastasis patterns and prognosis after complete resection of retroperitoneal liposarcoma - Gao, Xiaofeng; Ding, Pingan; Zhang, Zhidong; Li, Yong; Zhao, Qun; Wang, Dong; Zhao, Xuefeng; Liu, Yu; Tan, Bibo (Frontiers in Oncology, 2023)
Objective To analyze the recurrence and metastasis patterns and prognosis after complete resection of retroperitoneal liposarcoma. Methods The clinical postoperative follow-up data and results of patients who underwent complete resection of retroperitoneal liposarcoma from September 10, 2014, to September 8, 2021, at Hebei Medical University hospital were collected retrospectively. Results A total of 60 patients with complete resection of retroperitoneal liposarcoma, including 33 cases of retroperitoneal liposarcoma recurrence, 2 cases of liver metastasis, and 1 case of lung metastasis, were included. The results showed that 100% of the recurrent sites were located in the primary region of the tumor, with most recurrences located near the kidney, paracolic sulci, and iliac vessels. Three patients had distant metastasis without obvious recurrence on imaging examination. The pathological type of retroperitoneal liposarcoma, Ki67 expression, and presence of serum albumin were risk factors for recurrence and metastasis after complete resection of retroperitoneal liposarcoma. The malignancy and Ki67 expression were independent risk factors for recurrence and metastasis as well as for overall survival of patients undergoing complete resection of retroperitoneal liposarcoma. Conclusion Complete resection remains the most effective method to treat retroperitoneal liposarcoma. Patients with pathological types of retroperitoneal liposarcoma showing dedifferentiation, pleomorphism, mixed type, and high Ki67 expression should be closely monitored and observed after complete resection, especially for imaging changes in the primary tumor area.